KEJAHATAN TERORGANISASI LINTAS-NEGARA DI EROPA PASCABREXIT, 2016–2022 - Iwan Sulistyo (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
This article elaborates transnational organized crime (TOC) in Europe after the UK's exit from membership in the European Union (EU) or better known as British Exit (Brexit). Focusing on the highlights from 2016 to 2022, the elaboration is limited to explanations regarding the definitions, policies, and forms of TOC. Presenting a descriptive-qualitative study, the author uses secondary data in the form of various credible documents mainly issued by the EU, EUROPOL (especially the European Union Serious and Organized Crime Threat Assessment (SOCTA) document) in 2017 and 2021, as well as data from the UNODC. The argument that the writer puts forward is based on the Zabyelina dan Đorđević’s thoughts, namely their assumptions in a liberal institutionalist perspective. In addition, the United Nations Convention against Transnational Organized Crime and the Protocols Thereto (UNCTOC) assists the author in explaining the cooperation carried out by the EU with other partners to combat the TOC threats. The results of this study indicate that the UNCTOC definition is still being adopted by Europe. The policy shift occurred in the adjustment of the rule of law, particularly between the UK and the EU, as a consequence of Brexit.